From the Magdala Stone to the Syriac Bema : Mutual Influences between the Liturgical Space in the Early Synagogue and Church - Talgam, Rina (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
This book sheds light on the reciprocal relations between liturgical performance and the physical spaces in which they took place in synagogues and churches in antiquity. The kernel of the manuscript revolves around a decorated stone that was found during the excavations of a synagogue dated to the first century CE at Magdala on the shore of the Sea of Galilee. The book displays how this important archaeological discovery radically transforms our understanding of the changes in the shape of the liturgical space and the liturgical furniture in the places of assembly of the two sister faiths, Judaism and Christianity. See Less